Fortification of Iron Oxide as Sustainable Nanoparticles: An Amalgamation with Magnetic/Photo Responsive Cancer Therapies - Rethi L; Rethi L; Liu CH; Hyun TV; Chen CH; Chuang EY (International Journal of Nanomedicine, 2023)
Lekha Rethi,1,2,* Lekshmi Rethi,2,* Chia-Hung Liu,3,* Tin Van Hyun,4,5 Chih-Hwa Chen,1,2,6 Er-Yuan Chuang1,2,7 1Graduate Institute of Biomedical Materials and Tissue Engineering, College of Biomedical Engineering, Taipei Medical University, Taipei, 11031, Taiwan; 2International PhD Program in Biomedical Engineering, College of Biomedical Engineering, Taipei Medical University, Taipei, 11031, Taiwan; 3Department of Urology, School of Medicine, College of Medicine, Taipei Medical University, Taipei, 11031, Taiwan; 4International PhD Program in Medicine, College of Medicine, Taipei Medical University, Taipei, 11031, Taiwan; 5Department of Interventional Cardiology, Thong Nhat Hospital, Ho Chi Minh City, 700000, Vietnam; 6Department of Orthopedics, Taipei Medical University – Shuang Ho Hospital, New Taipei City, Taiwan; 7Cell Physiology and Molecular Image Research Center, Wan Fang Hospital, Taipei Medical University, Taipei, Taiwan*These authors contributed equally to this workCorrespondence: Er-Yuan Chuang, Email eychuang@tmu.edu.twAbstract: Due to their non-toxic function in biological systems, Iron oxide NPs (IO-NPs) are very attractive in biomedical applications. The magnetic properties of IO-NPs enable a variety of biomedical applications. We evaluated the usage of IO-NPs for anticancer effects. This paper lists the applications of IO-NPs in general and the clinical targeting of IO-NPs. The application of IONPs along with photothermal therapy (PTT), photodynamic therapy (PDT), and magnetic hyperthermia therapy (MHT) is highlighted in this review’s explanation for cancer treatment strategies. The review’s study shows that IO-NPs play a beneficial role in biological activity because of their biocompatibility, biodegradability, simplicity of production, and hybrid NPs forms with IO-NPs. In this review, we have briefly discussed cancer therapy and hyperthermia and NPs used in PTT, PDT, and MHT. IO-NPs have a particular effect on cancer therapy when combined with PTT, PDT, and MHT were the key topics of the review and were covered in depth. The IO-NPs formulations may be uniquely specialized in cancer treatments with PTT, PDT, and MHT, according to this review investigation.Keywords: cancer, hyperthermia, iron oxide, magnetic hyperthermia, photodynamic therapy, photothermal therapy, near-infrared